[Prospekt] Historical sketch of the rise, progress, and decline of the Reformation in Poland; and of the influence which the scriptural doctrines have exercised on that country, in literary, moral, and political respects: in 2 volumes - Krasiński, Walerian (print. for the author, and sold by Murray, Ridgway, 1840)
Dotyczy subskrypcji na drugi tom dzieła Waleriana Krasińskiego.
by Valerian Krasinski.
Keywords: Wielka Emigracja; Emigracja polityczna; Polska; Polacy za granicą; Wielka Brytania; Reformacja; historia; Edytorstwo; Wydawnictwa; Londyn (Wielka Brytania)